Obnova kulturne baštine u Bosni i Hercegovini kao osnova za interkulturalni dijalog i razvoj turizma - Ćorović, Adi; Obralić, Ahmed (Turizam, 2021)
This study deals with the buildings and sites destroyed during the war in Bosnia and Herzegovina, mostly carrying cultural and historical importance. In the last two decades in Bosnia and Herzegovina, there has been an actual reconstruction or restoration of cultural heritage, some of which have been included on the UNESCO World Heritage List. Indeed, "facsimile" reconstruction is often the case, based on the concept "as it was, where it was". Citizens of other faiths and nationalities have often given material and/or moral support to the reconstruction of "different" religious sites, confirming the thesis that they associate one part of their identity with "different". It was the first major war in Europe after World War II, where a great number of cultural goods were destroyed as symbols related to the identities of entire nations. Therefore, the response related to the reconstructions was similar to Europe's response after 1945 and represented a contribution to reconciliation, alleviation of collective trauma, and the development of intercultural dialogue and tourism. The study required an observation method for data collection. Based on conducted observations, the archival method was used for the investigation of documents and textual material, finding data in form of historical documents on architects, designers, the purpose of the settings, constructions, reconstructions, their interaction with areas, proofs on heritage values, and significance for the tourism of Bosnia and Herzegovina. All the aforementioned confirms the thesis that from today's perspective, the restored or reconstructed areas are the bearers of intercultural dialogue and the tourist potential of local communities and that reconstruction as the method has a very big role in the peace-building process.